Clinical effects of CD45 on the prognosis of extramedullary myeloma relapse. (18th September 2019) - Oka, Satoko; Ono, Kazuo; Nohgawa, Masaharu
Abstract: What is known and objectives: The incidence of extramedullary relapse (EMR) arising during the clinical course of multiple myeloma (MM) has increased in recent years. Therefore, we herein investigated the effects of immunophenotyping on the prognosis of MM patients with EMR. Methods: We conducted a retrospective review on data collected from MM patients with EMR between January 2007 and December 2018 at the Japanese Red Cross Society Wakayama Medical Center. Patient characteristics at the diagnosis of EMR, the prognostic significance of immunophenotyping and other factors were evaluated. Results and discussion: Extramedullary relapse was detected in 55 of 231 patients (23.8%). At the diagnosis of EMR, CD45, the leucocyte common antigen, was detected in 54.5% of cases. CD45 negativity in bone marrow correlated with thrombocytopenia and higher serum LDH levels. Moreover, high‐risk cytogenetics was more frequently observed in CD45− than in CD45+ patients. A univariate analysis showed that overall survival (OS) was significantly shorter in CD45− than in CD45+ patients. Thrombocytopenia, higher serum LDH levels and high‐risk cytogenesis were also associated with shorter OS. A multivariate analysis confirmed that CD45 negativity, higher serum LDH levels and high‐risk cytogenesis were independent adverse prognostic factors for OS. A Kaplan‐Meier analysis revealed the potential of CD45− as a prognostic factor in patients with EMR and that it correlated with shorter survival. What is new and conclusion: The present results showed that the expression of CD45 in the neoplastic plasma cells of MM patients with EMR was associated with patient prognosis independent of other prognostic factors. The establishment of a treatment strategy for EMR patients with CD45− MM cells is needed to improve poor outcomes. Abstract : We investigated the effects of immunophenotyping on the prognosis of MM patients with EMR. Fifty‐five patients with EMR were examined, and the prognostic significance of immunophenotyping and other factors was evaluated. A univariate analysis showed that OS was significantly shorter in CD45‐ than in CD45+ patients. Thrombocytopenia, higher serum LDH levels, and high‐risk cytogenesis were also associated with shorter OS. A multivariate analysis confirmed that CD45 negativity, higher serum LDH levels, and high‐risk cytogenesis were independent adverse prognostic factors for OS. A Kaplan‐Meier analysis revealed the potential of CD45‐ as a prognostic factor in patients with EMR and that it correlated with shorter survival. The present results demonstrated that the expression of CD45 in neoplastic plasma cells from MM patients with EMR was associated with their prognosis independent of other prognostic factor.